The cellular protrusions for inter-cellular material transfer: similarities between filopodia, cytonemes, tunneling nanotubes, viruses, and extracellular vesicles - Hu, Hooi Ting; Nishimura, Tamako; Kawana, Hiroki; Dante, Rachelle Anne So; D’Angelo, Gisela; Suetsugu, Shiro (Frontiers in Cell and Developmental Biology, 2024)
Extracellular vesicles (EVs) are crucial for transferring bioactive materials between cells and play vital roles in both health and diseases. Cellular protrusions, including filopodia and microvilli, are generated by the bending of the plasma membrane and are considered to be rigid structures facilitating various cellular functions, such as cell migration, adhesion, and environment sensing. Compelling evidence suggests that these protrusions are dynamic and flexible structures that can serve as sources of a new class of EVs, highlighting the unique role they play in intercellular material transfer. Cytonemes are specialized filopodia protrusions that make direct contact with neighboring cells, mediating the transfer of bioactive materials between cells through their tips. In some cases, these tips fuse with the plasma membrane of neighboring cells, creating tunneling nanotubes that directly connect the cytosols of the adjacent cells. Additionally, virus particles can be released from infected cells through small bud-like of plasma membrane protrusions. These different types of protrusions, which can transfer bioactive materials, share common protein components, including I-BAR domain-containing proteins, actin cytoskeleton, and their regulatory proteins. The dynamic and flexible nature of these protrusions highlights their importance in cellular communication and material transfer within the body, including development, cancer progression, and other diseases.